2011
DOI: 10.1002/pmic.201000483
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling between CNE‐2 and its strongly metastatic subclone S‐18 and functional characterization of HSP27 in metastasis of nasopharyngeal carcinoma

Abstract: Metastasis to secondary sites remains the leading cause of nasopharyngeal carcinoma (NPC)-associated death. In order to identify the candidate protein(s) responsible for the differential metastatic capacity, the protein expression profiling between NPC cell line CNE-2 and its highly metastatic subclone S-18 were compared by 2-DE. In total, 18 spots were differentially expressed between these two cell lines. Among all, seven proteins were identified with further MS analysis. Western blotting further validated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Two sets of cell lines, 5-8F (high tumorigenic and metastatic potential) and 6-10B (low tumorigenic and metastatic potential), which were derived from the NPC cell line SUNE-1 [21], and S18 (high tumorigenic and metastatic potential) and S26 (low tumorigenic and metastatic potential), which were derived from CNE-2 cells [22,23], represent good models for investigating the metastasis of NPC. For the first time, we compared these high metastatic potential and low metastatic potential cell lines (5-8F vs. 6-10B and S18 vs. S26) using microarrays to identify dysregulated lncRNAs that participate in NPC tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Two sets of cell lines, 5-8F (high tumorigenic and metastatic potential) and 6-10B (low tumorigenic and metastatic potential), which were derived from the NPC cell line SUNE-1 [21], and S18 (high tumorigenic and metastatic potential) and S26 (low tumorigenic and metastatic potential), which were derived from CNE-2 cells [22,23], represent good models for investigating the metastasis of NPC. For the first time, we compared these high metastatic potential and low metastatic potential cell lines (5-8F vs. 6-10B and S18 vs. S26) using microarrays to identify dysregulated lncRNAs that participate in NPC tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most important etiologic factors implicated in NPC pathogenesis are genetic aberrations, Epstein-Barr viral infection and chemical carcinogen exposure. The aberrantly expressed genes induced by these factors have been shown to play an important role in the development and progression of NPC [1][2][3][4][5][6][7][8]. However, the molecular mechanisms of NPC are not still fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HSP27 seems to promote metastasis formation through its effect on cytoskeletal components and to favor resistance to chemotherapeutic agents (Hino et al 2000 ;Katoh et al 2000 ;Li et al 2011 ). Choi et al showed that HSP27 expression was directly responsible for colorectal cancer cell resistance to the chemotherapeutic agent irinotecan.…”
Section: Hsp27: Favors Fibrosismentioning
confidence: 99%